The social media strategist : build a successful program from the inside out - Barger, Christopher (McGraw-Hill, 2012)
Conquer the unique challenges of driving social media success within a large company From the social media director who built successful programs at both GM and IBM, The Social Media Strategist provides the tools you need to meet all the challenges of building a social media strategy in a large company, which include corporate culture, legal barriers, and the kind of bureaucratic resistance that that are unique to large organizations. The Social Media Strategist explains how to get legal departments to say "yes" to social media programs; get employees engaged without exposing the organization to risk; build "buzz" that parallels business goals; and avoid the internal turf wars that can doom new initiatives. Christopher Barger is Senior Vice President of Global Programs at Voce Connect, a division of Porter Novelli, which assists clients around the world in developing social media programs and strategies. He spent four years as Director of Global Social Media at General Motors, and he served as IBM's "blogger-in-chief," playing a crucial role in developing IBM's online presence.